A Recombinant Fragment of Human Surfactant Protein D induces Apoptosis in Pancreatic Cancer Cell Lines via Fas-Mediated Pathway - Kaur, Anuvinder; Riaz, Muhammad Suleman; Murugaiah, Valarmathy; Varghese, Praveen Mathews; Singh, Shiv K.; Kishore, Uday (Frontiers in Immunology, 2018)
Human Surfactant Protein (SP-D) is a potent innate immune molecule, which is emerging as a key molecule in the recognition and clearance of altered and non-self targets. Previous studies have shown that a recombinant fragment of human SP-D (rfhSP-D) induced apoptosis via p53 mediated apoptosis pathway in an eosinophilic leukemic cell line, AML14.3D10. Here, we report the ability of rfhSP-D to induce apoptosis via TNF-α/Fas-mediated apoptosis pathway regardless of the p53 status in human pancreatic adenocarcinoma using Panc-1 (p53mt), MiaPaCa-2 (p53mt), and Capan-2 (p53wt) cell lines. Treatment of these cell lines with rfhSP-D for 24 h caused growth arrest in G1 cell cycle phase and triggered transcriptional upregulation of pro-apoptotic factors such as TNF-α and NF-B. Translocation of NF-B from the cytoplasm into the nucleus of pancreatic cancer cell lines was observed via immunofluorescence microscopy following treatment with rfhSP-D as compared to the untreated cells. The rfhSP-D treatment caused upregulation of pro-apoptotic marker Fas, as analyzed via qPCR and western blot, which then triggered caspase cascade, as evident from cleavage of caspase 8 and 3 analyzed via western blot at 48 h, and subsequent, apoptosis of the cells. The cell number following the rfhSP-D treatment was reduced in the order of Panc-1 (~67%) > MiaPaCa-2 (~60%) > Capan-2 (~35%). Our studies appear to suggest that rfhSP-D can be used to therapeutically target pancreatic cancer cells irrespective of their p53 phenotype.